2014
DOI: 10.12688/f1000research.5099.1
|View full text |Cite
|
Sign up to set email alerts
|

One year adjustable intragastric balloon: safety and efficacy of the Spatz3 adjustable balloons

Abstract: Discuss this article AbstractThe Spatz3 Adjustable balloon system is approved for 1 year Background: implantation and allows multiple changes in the balloon volume during the course of implantation. Other intragastric balloons are currently approved for 6 months and their balloon volumes cannot be adjusted after implantation.To determine the efficacy and safety of the Spatz3 adjustable balloon Aim: system.Seventy seven consecutive patients (66 females and 11 males) in Methods: two medical centers were implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
2
8
2
Order By: Relevance
“…Only two removals (1.11%) were performed due to severe symptoms (excessive vomiting) in patients who did not wish to do the downward adjustment and decided to quit the treatment. The incidence of early removal in the present study was 7.77%, being similar to that observed in other studies conducted with Spatz, Machytka et al (2014) [6] observed 7.79% and Brooks et al (2014) [14] 5.47%. However, this rate is higher than the observed in studies conducted with conventional IGB, Genco et al (2005) [9] observed 0.44%, Lopez-Nava et al (2011) [12] 0.8% and Sallet et al (2004) [1] 3.4% .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Only two removals (1.11%) were performed due to severe symptoms (excessive vomiting) in patients who did not wish to do the downward adjustment and decided to quit the treatment. The incidence of early removal in the present study was 7.77%, being similar to that observed in other studies conducted with Spatz, Machytka et al (2014) [6] observed 7.79% and Brooks et al (2014) [14] 5.47%. However, this rate is higher than the observed in studies conducted with conventional IGB, Genco et al (2005) [9] observed 0.44%, Lopez-Nava et al (2011) [12] 0.8% and Sallet et al (2004) [1] 3.4% .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, patients who underwent downward adjustment (n = 8; 4.44%), all, without exception, completed the minimum 9 months treatment, similar to what was observed in other Spatz (r) IGB studies. [6,14] Thus, it seems that the downward balloon adjustment may contribute to a better adaptation and a lower early removal rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience alleviating intolerance and preventing early extraction with balloon volume down adjustments is consistent with previously published Spatz3 studies [22][23][24][25]. Similarly, our use of upward adjustments (for decreased balloon effect) which added a mean 6.5kg extra weight loss is consistent with previously published Spatz3 data, which reported additional weight loss after upward adjustments of 8.2 kg, 8.9 kg, 5 kg and 5.7 kg [22][23][24][25]. These balloon volume manipulations have produced an impressive percentage of patients that have a successful outcome-79% (297/376) had > 25% EWL in our retrospective series.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have reported the results of the Spatz adjustable balloon system with wt losses of 24.4 kg (48.8% EWL), 21.6 kg (45.7% EWL), 17.2 kg (42.9% EWL), and 16.3 kg (67.4% EWL), respectively [20][21][22][23]. It is possible that alleviating intolerance with a downward adjustment and renewing wt loss after balloon upward adjustment may be able to improve weight loss results.…”
Section: Introductionmentioning
confidence: 99%